2021
DOI: 10.1016/j.cyto.2021.155702
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-37 is down-regulated in serum of patients with severe coronavirus disease 2019 (COVID-19)

Abstract: Pro-inflammatory and anti-inflammatory cytokines are indicated to play a prominent role in mediating the immunopathogenesis of coronavirus disease 19 (COVID-19). Interleukin (IL-37) is one of the anti-inflammatory cytokines that has been proposed to be involved in disease progression but the data are not overwhelming. Therefore, a case-control study was performed to analyze IL-37 levels in serum of 100 patients with severe COVID-19 and 100 blood donors (control group). Median age was significantly higher in CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…The data revealed that SNP rs3811046 detection was significantly higher in patients (61%) when compared to controls (38.0%), which was also the case with SNP rs3811047 (patients 39% vs. controls 24%). In contrast to the previous findings, a more recent study showed that IL-37 expression was suppressed in COVID-19 patients but was prominent in obese patients ( Ahmed and Ad’hiah, 2021b ). Therefore, it is evident that low IL-37 plasma levels could be used as COVID-19 severity marker.…”
Section: Correlation Between Interleukin 37 and Covid-19contrasting
confidence: 84%
“…The data revealed that SNP rs3811046 detection was significantly higher in patients (61%) when compared to controls (38.0%), which was also the case with SNP rs3811047 (patients 39% vs. controls 24%). In contrast to the previous findings, a more recent study showed that IL-37 expression was suppressed in COVID-19 patients but was prominent in obese patients ( Ahmed and Ad’hiah, 2021b ). Therefore, it is evident that low IL-37 plasma levels could be used as COVID-19 severity marker.…”
Section: Correlation Between Interleukin 37 and Covid-19contrasting
confidence: 84%
“…However, in another study, Ahmed AA and Ad'hiah AH demonstrated lower serum levels of IL-37 and its possible association with a higher risk of disease in COVID-19 patients. Additionally, IL-37 was significantly correlated with vitamin D levels [ 231 ]. Second, they discovered that mutations of the IL37 genes are also associated with the susceptibility to the COVID-19 [ 232 ].…”
Section: The Pathogenesis Of Il-36 Il-37 and Il-38 In Covid-19mentioning
confidence: 99%
“… 22 Recently, IL‐37, an anti‐inflammatory cytokine functionally related to IL‐38, showed low levels in serum of severely ill COVID‐19 patients, and accordingly it has been suggested that low levels of IL‐37 are associated with disease risk. 10 Moreover, lower levels of IL‐38 were found in severely ill patients compared to patients with nonsevere disease. 11 In the current study, increased levels of IL‐38 were found in severe/critical patients over 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been proposed that IL‐38 can ameliorate inflammation by inhibiting the production of certain proinflammatory cytokines such as IL‐17 and IL‐22 22 . Recently, IL‐37, an anti‐inflammatory cytokine functionally related to IL‐38, showed low levels in serum of severely ill COVID‐19 patients, and accordingly it has been suggested that low levels of IL‐37 are associated with disease risk 10 . Moreover, lower levels of IL‐38 were found in severely ill patients compared to patients with nonsevere disease 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation